Porcine cytochrome 2A19 and 2E1 - Burkina, Viktoriia; Rasmussen, Martin Krøyer; Oliinychenko, Yelyzaveta; Zamaratskaia, Galia (Basic & clinical pharmacology & toxicology, 2019)
Cytochrome P450 (CYP) is a major group of enzymes, which conduct Phase I metabolism. Among commonly used animal models, the pig has been suggested as the most suitable model for investigating drug metabolism in human beings. Moreover, porcine CYP2A19 and CYP2E1 are responsible for the biotransformation of both endogenous and exogenous compounds such as 3-methylindole (skatole), sex hormones and food compounds. However, little is known about the regulation of porcine CYP2A19 and CYP2E1. In this MiniReview, we summarise the current knowledge about the regulation of porcine CYP2A19 and CYP2E1 by environmental, biological and dietary factors. Finally, we reflect on the need for further research, to clarify the interaction between active feed components and the porcine CYP system.
Keywords: phase I enzymes; Biotransformation; Humans; cytochrom P450 CYP2A6; Animal Feed; Sequence Homology; lidé; pohlavní steroidní hormony; zvířata; Cytochrome P-450 CYP2E1; Xenobiotics; Swine; Skatole; bioactive compounds; skatol; cytochrom P-450 CYP2E1; krmivo pro zvířata; pig; skatole; Gonadal Steroid Hormones; xenobiotika; Cytochrome P-450 CYP2A6; biotransformace; Animals; prasata; sekvenční homologie